Influences of screw dislocations on electroluminescence of AlGaN/AlN-based UVC LEDs - Dong Liu; Sang June Cho; Huilong Zhang; Corey R. Carlos; Akhil R. K. Kalapala; Jeongpil Park; Jisoo Kim; Rafael Dalmau; Jiarui Gong; Baxter Moody; Xudong Wang; John D. Albrecht; et al. (AIP Advances, 2019)
We investigated two types of threading dislocations in high Al-composition Al0.55Ga0.45N/AlN multiple quantum well (MQW) structures grown on AlN substrate for electrically injected deep ultraviolet light-emitting diodes (LEDs). The surface morphology and defects electrical characteristics of the MQW LED structures were examined via conductive atomic force microscopy (CAFM). We found that the disparity between photoluminescence (PL) and electroluminescence (EL) spectra in terms of light emission output and wavelength shift are attributed to the existence of the surface hillocks, especially to the ones that have open-core dislocations. The open-core dislocations form current leakage paths through their defect states and the composition inhomogeneity (i.e., Ga rich) at the dislocation sites are responsible for the light emission at longer wavelengths.